English Language Acquisition As A Foreign Language on Coachman of Cidomo In Gili Trawangan Lombok - Jumadil, Jumadil; Emzir, Emzir; Lustyantie, Ninuk (International Journal for Educational and Vocational Studies, 2020)
This paper discusses the acquisition of English as a Foreign language on coachman of cidomob. In this study  the researchers applied a case study. The purpose of this study was to find deeper, how Cidomo coaches acquired English, the obstacles faced in acquiring English, and the strategy of English acquisition used. To get the data in these study researchers conducted observations in three months and in-depth interviews with two informants who had been previously chosen. After obtaining the data  the researcher conducted data reduction, data presentation and conclusions by using Mile & Huber man’s data analysis technique. The  result  it  found that  both of  coachman Cidomo  had acquired  English as  foreigners by listening to the native speakers, known through their native friends, imitating it and afterwards practicing with the tourist and their  native friends, while the obstacles faced by them were pronunciation, changing sounds of several phonemes such as phoneme F to P, V to  F and B to  P and the difficulty in memorizing vocabulary because they have been acquiring that second  language since they were  forty years old. Further, the strategy of English acquisition they applied respectively started from  memorizing utterances  such as  greetings, asking for permission, saying  goodbye, and after that they memorizing vocabularies related to their job ranging from objects to the natural environment around them to  complete and improve their second language acquisition.